Incidence and predictors of mild cognitive impairment (MCI) within a multi-ethnic Asian populace: a community-based longitudinal study - Norlela Mohd Hussin (BMC Public Health, 2019)
Abstract Background Limited information is available from longitudinal studies regarding the predictors and incidence of MCI in older Asian adults. Thus, a community-based longitudinal study was conducted to determine the incidence of MCI among multi-ethnic older adults in Malaysia. The role of health and lifestyle as predictors of MCI was also examined. Methods Analysis of data obtained from the Towards Useful Aging (TUA) study (2014–2016), wave 1 (baseline) and wave 2 (1½ years of follow-up) was conducted. For the baseline, comprehensive, interview-based questionnaires were administered to 1227 subjects who were 60 years old and above. MCI is a unique transitional state between normal ageing and dementia. MCI characteristics include a decline and disturbance of cognition, minimal impairment of complex activities, ability to perform regular daily functions, and absence of dementia. The incidence of MCI was assessed using comprehensive neuropsychological batteries. The study then performed a logistic regression analysis to examine the effect of each possible predictor of MCI. This analysis began with univariate analyses and a separate review of the effect of every variable. Binary logistic analyses followed hereafter. Results During the follow-up after 1½ years, 179 (14.6%) of the participants who did not exhibit MCI at baseline were observed to have developed MCI. Among the participants who did not exhibit MCI at baseline, the incidence rate was 10.5 per 100 person-years. Male sex and lack of engagement in mental activities were predictors of MCI among participants without MCI at baseline. Conclusion After the 1½-year follow-up, the incidence rate for MCI was considerably high among the respondents. Being male and being less engaged in mental activities were predictors of the occurrence of MCI. Mental activities need to be promoted for the prevention of MCI incidence among older adults.